Nalar Fikih Sufistik Fatwa Majelis Ulama Indonesia (MUI) dalam Merespons Pandemi Covid-19 - Agustina, Arifah Millati (IAIN Surakarta, 2020)
During the Covid-19 pandemic period, the Indonesian ulama council (Majlis Ulama Indonesia, MUI) issued fatwas related to worship practices particularly in terms of communal prayers such as Ied prayers and Friday prayer. This fatwa is important because the worship of Muslims is much congregated held. This article aims to uncover while testing about whether the MUI fatwa produced during the pandemic era, particularly in terms of the Muslims congregated worshipping practices, contains only sharea dimension or also Sufistic dimension. The study uses the Sufistic fiqh approach of al-Ghazali that posits the existence of unification between fiqh (islamic jurispudence) and Sufism for which the product of the law issued contains the dimensions of both fiqh and at once Sufism. The study found that the fatwa of MUI was grounded three dimensions; first, the dimension of rage evidenced by the use of the religious doctrine in formulating fatwas; second, the dimension of logic attested by the existence of rationality and dynamization in the production, for example keeping shaf (lines) on congregational prayer to avoid the physical interaction, social distancing; third, the Sufistic dimension as evidenced by an appeal to Muslims to frequently and multiply chant (dhikr) bringing peace of mind and peace of mind. The purpose of the existence of these three dimensions is to improve the welfare of all people, generally the Indonesian people from Covid-19.